Efficacy of morning-only dose compared with split-dose polyethylene glycol electrolyte solution in bowel cleansing for afternoon colonoscopy - Shrestha, Roshan; Karki, Sanjit; Sharma, Yuba Raj (Journal of Patan Academy of Health Sciences, 2022)
Introduction: The efficacy of colonoscopy in detecting abnormalities within the colon is highly dependent on the adequacy of the bowel preparation. The objective of this study was to compare the efficacy and tolerability of morning only dose vs split-dose administration of polyethylene glycol (PEG) solution for colon cleansing in patients undergoing afternoon colonoscopy. Method: This was a comparative study conducted in Department of Medicine, Patan Academy of Health Sciences (PAHS), Patan Hospital, Nepal from November 2021 to June 2022. The ethical clearance was obtained from the Institutional Review Committee. Informed consent was taken from the patients. Patients aged >18 y undergoing elective colonoscopy were randomly assigned to one of the two bowel preparation regimens- morning only or split-dose of PEG. The adequacy of bowel preparation was assessed by the endoscopist using Boston Bowel Preparation scale. Preparation to colonoscopy (PC) interval, adverse events and risk factors for poor bowel preparations were noted. Result: In this study, 110 patients were included in the final analysis- 55 received morning only regimen and 55 received split-dose. Mean Boston bowel preparation scales of Morning only and Split-dose regimen were 7.60 and 7.09 respectively (p= 0.019). Split-dose group had significant sleep disturbances compared to Morning only regimen (p< 0.001), whereas nausea occurred significantly more often in Morning only regimen (p=0.012). Preparation to colonoscopy interval between 4-6 hours resulted in better bowel cleansing compared to PC interval of greater than 6 hours. Conclusion: Morning-only bowel preparation is more effective than Split-dose for achieving adequate colon cleansing for afternoon colonoscopy.